Reflections on the transformation of education for the knowledge age - Marlene SCARDAMALIA (Ediciones Universidad de Salamanca, 2016)
New knowledge media provide new opportunities and means for addressing fundamental problems in education. But there are now so many designs for educational environments that choosing between them is difficult. Advancing the state of the art will require greater clarity regarding different possibilities and the ways in which designs reflect different underlying theoretical frameworks and research bases.  This article highlights a particular form of online environment, a knowledge building environment (KBE), and contrasts it with online environments designed more specifically for course delivery, computer-mediated projects, and distance learning. Although a KBE can be used for these purposes, its distinctive strengths emerge in contexts-educational and other-where the emphasis is on knowledge creation and sustained idea improvement.